Assessing the Learning Administration of Higher Education Institutions by Graduates' Turn-Out and Learning Outcomes: Theory and Practice - Aleksandr I. Bokarev; Еlena S. Denisova; Ivan A. Ignatovich; Aleksandr Yu. Kazakov (National Research Mordova State University, 2021)
Introduction. This article describes how universities are fulfilling their training assignments. Its relevance is determined by the growing need of teachers to correlate the learning results of specialists-to-be with learning assignments. The aim of the article is to describe a method for assessing the learning management system of higher education institutions by analysing learning outcomes and graduates' turn-out. Materials and Methods. The study relies on the collection and analysis of the results of specialists' training between 2015 and 2019. The joint use of the obtained data and methods of normative forecasting and interpolation allowed the authors to calculate and measure the intermediate results relative to the final ones, to build educational trajectories, which made it possible to evaluate the learning management system by dealing with training results and graduates turn-out. Results. For the first time the authors of the article showed that the measured results demonstrated not only the scope of specialists' training and graduation, but they evaluated management of the educational process and developed necessary management decisions to regulate standards and measures for specialists' training and graduation according to the specified final results. Discussion and Conclusion. The conclusions contribute to the development of the concept of learning management systems, provided that there are specified final results of the specialists' graduation. Findings are of interest to the scientific and pedagogical community, professors, teaching staff and leadership of educational institutions.